Modified porous-compact solid electrolyte and preparation method thereof
By preparing modified porous-tight solid electrolyte, a continuous conductive network is formed using a molten salt material modification layer and a pore-forming agent, the interfacial stress and low utilization problems caused by volume changes in alkali metal negative electrodes in lithium-ion batteries are solved, and the problem of high efficiency is improved. Battery magnification performance and stability.
Patent Information
- Application Number
- CN202411235015.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-04
AI Technical Summary
The energy density of lithium-ion batteries has reached the theoretical limit, and it uses combustible organic electrolyte, which has insufficient safety. The volume of alkali metal negative electrode changes violently under high current density, resulting in large interface stress/strain of electrolyte/electrode and poor interface wetting. The ion mobility efficiency is low, affecting the negative electrode utilization rate and battery rate performance.
By adopting the preparation method of modified porous-tight solid electrolyte, the molten salt material is flattened to the surface of the porous layer and heated to melt and decompose, a modified layer with low surface energy is formed, and the wetting property of the porous layer and the alkali metal negative electrode is improved. And a three-dimensional continuous ionic conductive network is formed through a pore-forming agent to improve ion migration efficiency.
It significantly improves the utilization rate and battery rate performance of alkali metal negative electrodes, improves the electrode reaction kinetics, reduces battery polarization, avoids the use of expensive and complex surface modification technology, and achieves high current density and large area capacity Stable cycle.
Smart Images

Figure CN119253034A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid electrolyte preparation, and more specifically, relates to a modified porous-dense solid electrolyte and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are widely used in mobile electronic devices and other fields due to their advantages such as long cycle life, low cost and fast response. However, the energy density of lithium-ion batteries has gradually reached its theoretical limit, and its safety is greatly reduced due to the use of flammable organic electrolytes. Solid-state alkali metal batteries use alkali metals as negative electrodes and solid-state ion conductors as electrolytes. They have high energy density and safety and are expected to replace lithium-ion batteries as the next generation of electrochemical energy storage technology. However, at high current densities (≥1.0mA cm -2 ) under low temperature conditions, the volume of the alkali metal negative electrode changes dramatically, resulting in large stress / strain at the electrolyte / electrode interface, and it is difficult to maintain good interfacial wettability, resulting in increased interfacial resistance; at the same time, the negative electrode bulk phase lacks continuous ion percolation paths, resulting in low ion migration efficiency and few effective reaction interfaces; these factors lead to low alkali metal utilization at the negative electrode and poor battery rate performance.
[0003] In the prior art, a porous-dense double-layer electrolyte is proposed that can construct a continuous ion permeation path to a certain extent and improve the ion migration efficiency. However, the interfacial wettability of the porous-dense double-layer electrolyte / alkali metal negative electrode interface is poor, and it cannot truly improve the low alkali metal utilization rate of the negative electrode and the poor battery rate performance. Summary of the invention
[0004] In view of the above defects or improvement needs of the prior art, the present invention provides a modified porous-dense solid electrolyte and a preparation method thereof, the purpose of which is to improve the utilization rate of alkali metals in the negative electrode to improve the battery rate performance.
[0005] To achieve the above object, according to a first aspect of the present invention, a method for preparing a modified porous-dense solid electrolyte is provided, comprising:
[0006] Spreading a molten salt material onto the surface of a porous layer of a porous-dense solid electrolyte, and performing a first heating until the molten salt material is melted; wherein the porous-dense solid electrolyte comprises a porous layer and a dense layer composed of solid electrolyte powder;
[0007] After the molten salt material is melted, it is heated for a second time to decompose the molten salt material. The decomposed product of the molten salt material adheres to the surface of the porous layer to obtain a modified porous-dense solid electrolyte.
[0008] Furthermore, the melting point of the molten salt material is 50°C to 500°C, and the decomposition temperature is 100°C to 700°C.
[0009] Furthermore, the preparation process of the porous-dense solid electrolyte includes:
[0010] The solid electrolyte powder and the pore former are stirred and mixed in an organic inert solvent, and then the organic inert solvent is evaporated to obtain a mixed powder;
[0011] Adding solid electrolyte powder to a tablet pressing mold and pressing it into a tablet as a dense layer precursor; evenly spreading the mixed powder on the surface of the dense layer precursor and pressing it into a green blank; wherein the mixed powder forms a porous layer precursor during the pressing process;
[0012] The green body is sintered to form a porous-dense solid electrolyte consisting of a porous layer and a dense layer.
[0013] Furthermore, the proportion of the pore-forming agent in the mixed powder is 10wt% to 33.3wt%.
[0014] Furthermore, the amount of the porous layer powder is 50 mg to 100 mg, and the amount of the dense layer powder is 100 mg to 500 mg.
[0015] Further, the solid electrolyte is a garnet-type oxide, β″-alumina, NASICON-type, argyrodite-type, alkali metal nitride or LiPON-type solid electrolyte;
[0016] The pore-forming agent is polyethylene oxide, polymethyl methacrylate, polyacrylonitrile, polyvinyl chloride, polyvinyl alcohol, polyvinyl acetate, polyacrylic acid, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, chitosan, methyl cellulose, starch, FeCl3, AlCl3, BiCl3, SbF3, SbCl3, S or SeS2.
[0017] According to a second aspect of the present invention, a modified porous-dense solid electrolyte is provided, wherein the modified porous-dense solid electrolyte is prepared by the modified porous-dense solid electrolyte preparation method described in any one of the first aspects.
[0018] According to a third aspect of the present invention, there is provided a method for preparing a composite alkali metal negative electrode, comprising:
[0019] The alkali metal is heated to a molten state and poured onto the surface of the porous layer of the modified porous-dense solid electrolyte to obtain a composite alkali metal negative electrode;
[0020] Wherein, the modified porous-dense solid electrolyte is prepared by the modified porous-dense solid electrolyte preparation method described in any one of the first aspects, or is the modified porous-dense solid electrolyte described in the second aspect.
[0021] Furthermore, the alkali metal is lithium, sodium or potassium.
[0022] According to a fourth aspect of the present invention, a composite alkali metal negative electrode is provided, and the composite alkali metal negative electrode is prepared by the composite alkali metal negative electrode preparation method described in the third aspect.
[0023] In general, the above technical solutions conceived by the present invention can achieve the following beneficial effects:
[0024] (1) The present invention finds that the prepared porous-dense solid electrolyte is directly used as the electrolyte of the solid alkali metal battery, and the wettability of the interface between the prepared porous-dense solid electrolyte and the alkali metal negative electrode is poor. Specifically, it is because the surface energy of the molten alkali metal is very high. If it is directly in contact with the porous-dense solid electrolyte, the contact angle is very large. Based on this, the modified porous-dense solid electrolyte preparation method of the present invention is to modify the surface of the porous-dense solid electrolyte by using a molten salt with a lower surface energy (which has a lower contact angle with the porous-dense solid electrolyte), spread the molten salt material on the porous layer surface of the porous-dense solid electrolyte, heat it until the molten salt material is melted, and then the molten salt material penetrates into the porous layer of the porous-dense solid electrolyte through capillary force. When further heated, the molten salt material decomposes, and the decomposed product adheres to the surface of the porous layer, thereby improving the wettability of the porous layer and the alkali metal negative electrode. In this way, the utilization rate of the alkali metal of the negative electrode can be improved, thereby improving the battery rate performance.
[0025] (2) The present invention uses molten salt to uniformly modify the surface of the porous-dense solid electrolyte, avoiding the use of complex and costly surface modification technologies such as magnetron sputtering, atomic layer deposition, and vapor deposition, and improves the wettability of the porous solid electrolyte with alkali metals in a simple and low-cost method.
[0026] (3) When the molten alkali metal negative electrode is composited with the modified porous-dense solid electrolyte, on the one hand, the molten alkali metal is uniformly adsorbed into the porous layer of the modified porous-dense solid electrolyte under the action of capillary force; on the other hand, the molten alkali metal also reacts with the decomposition products of the molten salt material attached to the surface of the porous layer during modification, chemically inducing the molten alkali metal to uniformly fill the porous structure. Under the combined action of this physical and chemical method, the contact / reaction area between the alkali metal and the solid electrolyte is effectively increased, which is beneficial to improving the charge transfer rate and the utilization rate of the alkali metal, thereby improving the battery rate performance.
[0027] (4) Preferably, at the set melting point and decomposition temperature of the molten salt material, the molten salt material can obtain a lower melt viscosity to penetrate into the porous solid electrolyte for uniform surface modification, and a sufficient decomposition rate to form active nanoparticles to induce subsequent molten alkali metal injection into the porous electrolyte layer.
[0028] (5) Furthermore, in the present invention, a solid electrolyte powder containing a pore-forming agent is integrated with a solid electrolyte powder and pressed into a green billet, and the pore-forming agent is removed by sintering. The sintering ensures that the porous layer and the dense layer have a high bonding strength. Therefore, a three-dimensional continuous ion conductive network is formed inside the obtained porous-dense solid electrolyte. Using it as an ion percolation path can improve the ion migration efficiency inside the alkali metal negative electrode and increase the electrochemical reaction active interface. Therefore, the stress / strain caused by the volume change of the alkali metal negative electrode is alleviated, the electrode reaction kinetics is enhanced, and the battery polarization is reduced.
[0029] (6) Preferably, the proportion of the pore former in the mixed powder is set so as to form an open porous structure while ensuring the integrity of the formed porous structure.
[0030] (7) Preferably, the mass of the porous layer and the dense layer powder is set so that the molten lithium can completely fill the porous layer without any residue on the surface; and the internal resistance of the battery can be reduced as much as possible while maintaining the strength of the porous structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The flowchart of the method for preparing the modified porous-dense solid electrolyte in the embodiment of the present invention.
[0032] Figure 2 Schematic diagram of the method for preparing a porous-dense solid electrolyte in an embodiment of the present invention.
[0033] Figure 3 SEM images of porous-dense LLZTO (PD-LLZTO) electrolytes prepared from mixed powders with different pore-forming agent mass ratios.
[0034] Figure 4 These are SEM images of molten lithium injected into porous LLZTO electrolyte with different porous layer powder dosages.
[0035] Figure 5 These are SEM images of the porous-dense LLZTO at different sizes in Example 1; wherein (a) and (b) are SEM images at 500 μm and 50 μm, respectively.
[0036] Figure 6 Schematic diagram of AgNO3 molten salt modification of porous LLZTO layer in Example 1.
[0037] Figure 7 This is an optical schematic diagram of AgNO3 molten salt infiltrating into porous LLZTO in Example 1.
[0038] Figure 8 This is an optical schematic diagram of the high-temperature decomposition of AgNO3 in the porous LLZTO layer in Example 1.
[0039] Fig. 9 This is an optical schematic diagram of molten Li metal infiltrating into the AgNO3-modified porous LLZTO layer in Example 1.
[0040] Fig.10 SEM images and EDX results of the porous LLZTO layer after molten Li infiltration in Example 1; wherein, (a) is the SEM result of the porous / dense LLZTO interface after molten Li filling, (b)-(d) are the corresponding EDX results of Ag, La and O, respectively; (e) and (f) are the SEM results of the porous layer after molten Li filling and the SEM results after local magnification, respectively, and (g) and (h) are the corresponding EDX results of Ag and La, respectively.
[0041] Fig.11 The cycle performance and critical current density test of the Li-Ag|PDP-LLZTO|Li-Ag lithium symmetric battery prepared and assembled according to Example 1 are as follows; wherein (a)-(c) represent 0.5 mA cm -2 @0.5mAh cm -2 、1.0mAcm -2 @0.5mAh cm -2 and 1.5mAcm -2 @0.75mAh cm -2 (D) is the critical current density test of Li symmetric battery.
[0042] Fig.12 The cycling performances of the Li-Ag|DP-LLZTO|LFP lithium iron phosphate solid-state lithium metal battery assembled according to Example 1 and the Li-Ag|LLZTO|LFP and Li|LLZTO|LFP lithium iron phosphate solid-state lithium metal batteries without porous structures; wherein (a)-(b) represent the cycling performances of the lithium iron phosphate full battery at 0.5C and 1.0C, respectively. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0044] In the present invention, the terms "first", "second", etc. in the present invention and the accompanying drawings are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence.
[0045] like Figure 1 As shown, an embodiment of the present invention provides a method for preparing a modified porous-dense solid electrolyte, comprising:
[0046] The molten salt material is spread onto the surface of the porous layer of the porous-dense solid electrolyte, and the molten salt material is heated for the first time until it melts; then the molten salt material is heated for the second time to decompose the melted molten salt material, and the decomposition products of the molten salt material adhere to the surface of the porous layer to obtain a modified porous-dense solid electrolyte; wherein the porous-dense solid electrolyte comprises a porous layer composed of solid electrolyte powder and a dense layer composed of solid electrolyte powder.
[0047] Preferably, the melting point of the molten salt material is 50°C to 500°C, and the decomposition temperature is 100°C to 700°C; the molten salt material within the limits of the melting point and decomposition temperature can obtain a lower melt viscosity to penetrate into the porous solid electrolyte for uniform surface modification, and a sufficient decomposition rate to form active nanoparticles to induce subsequent injection of molten alkali metal into the porous electrolyte layer.
[0048] In the embodiment of the present invention, Figure 2 As shown, the preparation of the above-mentioned porous-dense solid electrolyte includes:
[0049] The solid electrolyte powder and the pore former are stirred and mixed in an organic inert solvent, and then the solvent is evaporated to obtain a mixed powder;
[0050] The solid electrolyte powder is added to a tablet pressing mold and pressed into a tablet as a dense layer precursor, and then the pressing head is removed, and the mixed powder is added and evenly spread on the surface of the dense layer precursor, and the pressing head is reinserted to press the green blank into a green blank; wherein the green blank is composed of a porous layer precursor and a dense layer precursor;
[0051] The green body is sintered in a ceramic crucible to form a porous-dense solid electrolyte consisting of a porous layer and a dense layer.
[0052] Preferably, the solid electrolyte used as the solid electrolyte powder is a solid electrolyte that is chemically stable with alkali metals, so that it will not react with the subsequent molten alkali metal negative electrode, and the stability of the porous structure can be improved. For example, it can be a solid electrolyte that is chemically stable with alkali metals, such as garnet oxide, β″-alumina, NASICON type, argyrodite type, alkali metal nitride, LiPON type, etc.
[0053] The pore former is an artificially synthesized organic matter, natural polymer or inorganic matter that can burn, volatilize or sublimate to form an open porous structure after heating, and the residual matter after sintering has no effect on the conductivity of the solid electrolyte; synthetic organic matter, such as polyethylene oxide (PEO), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyvinyl chloride (PVC), polyvinyl alcohol (PVA), polyvinyl acetate (PVAc), polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and other organic matter that can be removed by oxidation combustion; natural polymers, such as chitosan, methyl cellulose, starch and other organic matter that can be removed by oxidation combustion; inorganic matter, such as FeCl3, AlCl3, BiCl3, SbF3, SbCl3, S, SeS2 and other inorganic matter that is easy to heat sublimate / volatilize.
[0054] Preferably, the proportion of the pore-forming agent in the porous layer precursor (or mixed powder) is 10 wt% to 33.3 wt%. Under such a proportion, an open porous structure can be formed while ensuring the integrity of the formed porous structure. Figure 3 As shown in the figure, the porous solid electrolyte prepared with 5% pore former has low porosity and many closed pores, which may cause the molten alkali metal to be unable to be fully injected into the porous structure, while the porous solid electrolyte prepared with 50% pore former cannot maintain structural integrity. The pore former ratios from 10% to 33.3% can maintain both open pore structure and structural integrity, among which the pore former ratio of 33.3% can maximize the porosity to increase the loading of alkali metal in the porous structure.
[0055] Preferably, the sintering temperature of the green blank in the ceramic crucible is 100°C to 1700°C, the heating rate during sintering is 1°C / min to 10°C / min, the holding time after sintering is 10min to 10h, and the cooling rate is 1°C / min to 10°C / min.
[0056] Preferably, the mass of the porous layer powder is 50 mg to 100 mg, and the mass of the dense layer powder is 100 mg to 500 mg. Figure 4 As shown in the figure, when the amount of porous layer powder is 30 mg, the porous layer is thin, and a large amount of molten lithium remains on the surface of the porous layer. When the amount of porous layer powder is 200 mg, the porous layer is thick, and the molten lithium cannot completely fill the porous layer. When the mass of the porous layer powder is 50 mg to 100 mg, the molten lithium can completely fill the porous layer, and there is no residue on the surface. For the dense layer, too little powder cannot maintain the strength of the entire structure, and too much powder can easily lead to excessive internal resistance of the battery, so 100 mg to 500 mg is selected.
[0057] In an embodiment of the present invention, a modified porous-dense solid electrolyte is further provided. The modified porous-dense solid electrolyte is prepared by the above-mentioned modified porous-dense solid electrolyte preparation method.
[0058] In an embodiment of the present invention, a method for preparing a composite alkali metal negative electrode is also provided, comprising:
[0059] The alkali metal is heated to a molten state and poured onto the surface of the porous layer of the modified porous-dense solid electrolyte prepared above to obtain a composite alkali metal negative electrode.
[0060] Among them, the alkali metal is an alkali metal such as lithium, sodium, and potassium.
[0061] In an embodiment of the present invention, a composite alkali metal negative electrode is further provided. The composite alkali metal negative electrode is prepared by the above-mentioned composite alkali metal negative electrode preparation method.
[0062] The present invention finds that the prepared porous-dense solid electrolyte is directly used as the electrolyte of the solid-state alkali metal battery, and the wettability of the interface between it and the alkali metal negative electrode is poor. Specifically, it is because the surface energy of the molten alkali metal is very high. If it is directly in contact with the porous-dense solid electrolyte, the contact angle is very large. Based on this, the modified porous-dense solid electrolyte preparation method of the present invention is surface-modified by using a molten salt with a lower surface energy (its contact angle with the porous-dense solid electrolyte is lower), and the molten salt material is flattened to the porous layer surface of the porous-dense solid electrolyte, and heated to the molten salt material melting, then the molten salt material penetrates into the porous layer of the porous-dense solid electrolyte by capillary force, and when further heated, the molten salt material decomposes, and the decomposed product is attached to the surface of the porous layer, thereby improving the wettability of the porous layer and the alkali metal negative electrode, so that the alkali metal utilization rate of the negative electrode can be improved, thereby improving the battery rate performance.
[0063] The present invention uses a molten salt-based method to uniformly modify the surface of a porous-dense solid electrolyte, avoiding the use of complex and costly surface modification technologies such as magnetron sputtering, atomic layer deposition, and vapor deposition, and improves the wettability of the porous solid electrolyte with alkali metals in a simple and low-cost method.
[0064] When the molten alkali metal negative electrode is composited with the modified porous-dense solid electrolyte, on the one hand, the molten alkali metal is uniformly adsorbed into the porous layer of the modified porous-dense solid electrolyte under the action of capillary force, and on the other hand, the molten alkali metal also reacts with the decomposition products of the molten salt material attached to the surface of the porous layer during modification, chemically inducing the molten alkali metal to uniformly fill the porous structure. Under the combined action of this physical and chemical action, the contact / reaction area between the alkali metal and the solid electrolyte is effectively increased, which is beneficial to improving the charge transfer rate and the utilization rate of the alkali metal, so as to improve the battery rate performance.
[0065] When preparing a porous-dense solid electrolyte, the present invention integrates a solid electrolyte powder containing a pore-forming agent with a solid electrolyte powder and presses them into a green billet, and removes the pore-forming agent by sintering. The sintering ensures that the porous layer and the dense layer have a high bonding strength, thereby forming a three-dimensional continuous ion conductive network as an ion percolation path, which can improve the ion migration efficiency inside the alkali metal negative electrode and increase the electrochemical reaction active interface. Therefore, the stress / strain caused by the volume change of the alkali metal negative electrode is alleviated, the electrode reaction kinetics is enhanced, and the battery polarization is reduced.
[0066] The method of the present invention is further described below with reference to specific embodiments.
[0067] Example 1
[0068] Preparation of garnet-type Li superionic conductor LLZTO (lithium lanthanum zirconium tantalum oxide, Li 6.4 LqCy 1.4 Ta 0.6 O 12 ) powder is used as the solid electrolyte powder, polymethyl methacrylate (PMMA) balls with a diameter of 10μm are used as pore formers, and the mass ratio of the solid electrolyte to the pore former is 2:1; the mixture is stirred and mixed at 700 rpm in an isopropanol solvent, and the solvent is removed by drying to obtain a mixed precursor powder. 0.05g of the powder and 0.1g of LLZTO powder are sequentially added to a tablet pressing mold, and pressed into a green billet at 300MPa. Subsequently, it is sintered at 1250°C in a magnesium oxide crucible for 20min, with a heating and cooling rate of 10°C / min to obtain a porous-dense LLZTO (PD-LLZTO) solid electrolyte; wherein the masses of the porous layer and the dense layer powder are 50mg and 100mg, respectively; as Figure 3 As shown, the SEM images of porous-dense LLZTO with different sizes are shown. Figure 5(a) and (b) are SEM images at 500μm and 50μm, respectively. AgNO3 is used as the surface modification material of the porous layer. After being heated to 250℃ to melt it, it penetrates into the porous layer and is further heated to 550℃ to decompose it, forming nano-Ag particles loaded on the surface of the porous layer to improve the lithium affinity of the porous layer. Subsequently, lithium metal is heated to 220℃ to melt it and alloy with the nano-Ag particles in the porous layer. Under the action of capillary force, the molten lithium penetrates into the porous layer to form a composite Li-Ag@LLZTO electrode, as shown in FIG. Figure 6-Figure 9 shown.
[0069] The decomposition reaction process of AgNO3 is as follows:
[0070]
[0071] The alloying reaction process is as follows:
[0072] xLi+Ag→Li x Ag
[0073] In Example 1, the SEM images and EDX results after molten Li infiltrated into the porous LLZTO layer are as follows: Fig.10 As shown, (a) is the SEM result of the porous / dense LLZTO interface after molten Li filling, (b)-(d) are the corresponding EDX results of Ag, La and O respectively; (e) and (f) are the SEM results of the porous layer after molten Li filling and the SEM results after local magnification, (g) and (h) are the corresponding EDX results of Ag and La respectively. The EDX result of Ag is used to reflect the distribution of the negative electrode, and the EDX result of La is used to reflect the distribution of the solid electrolyte. It can be seen that molten Li can penetrate to the interface between the porous layer and the dense layer and fill the pores of the porous layer, presenting a mutually penetrating morphology with the porous LLZTO. At the same time, no Ag nanoparticles were observed, indicating that the molten Li may have undergone a solid solution reaction with it. The EDX results show that the distribution of Ag and O elements is almost the same (the O element is mainly caused by the oxidation of Li during the sample transfer process, and to a certain extent represents the distribution of Li), proving that the continuous phase filling the pores is composed of Ag and Li, and is presumed to be a Li-Ag solid solution alloy. The magnified SEM image of the porous layer shows that the Li-Ag alloy has good wettability with LLZTO.
[0074] Fig.11 The cycle performance and critical current density test of the Li-Ag|PDP-LLZTO|Li-Ag lithium symmetric battery constructed according to Example 1 and assembled with porous-dense-porous LLZTO (PDP-LLZTO) were performed. Fig.11 (a)-(c) represent 0.5 mA cm -2 @0.5mAh cm -2、1.0mAcm -2 @0.5mAh cm -2 and 1.5mAcm -2 @0.75mAh cm -2 (d) shows the cycling performance of the Li symmetric battery; (e) shows the critical current density test of the Li symmetric battery; it can be seen that at 0.5 mA cm -2 @0.5mAh cm -2 Under the condition of 1.0 mA cm-2, the polarization of Li-Ag|LLZTO|Li-Ag battery increases continuously and short circuit fails after 120 h of cycling. On the contrary, Li-Ag|PDP-LLZTO|Li-Ag battery can be stably cycled for more than 6500 h. -2 The battery can still stably cycle for 1600 h, indicating that PDP-LLZTO has excellent long-term cycle stability. -2 The high current density and 0.75 mAh cm -2 The battery can also be stably cycled for more than 300 hours under the large surface capacity of LLZTO, indicating that the ion conductive network constructed by the porous LLZTO significantly increases the depth of lithium ion migration, improves the electrode reaction kinetics, relieves the stress / strain of the negative electrode, and improves the utilization rate of active materials, thereby achieving stable battery cycling under high current / high capacity. The critical current density (CCD) of the Li-Ag|PDP-LLZTO|Li-Ag battery reaches 2.1 mA cm -2 .
[0075] Fig.12 The cycling performance of the Li-Ag|PD-LLZTO|LFP lithium iron phosphate (LFP) solid-state lithium metal battery and the Li-Ag|LLZTO|LFP and Li|LLZTO|LFP batteries without porous structures assembled according to Example 1 is shown in FIG. Fig.12 (a)-(b) show the cycling performance of the lithium iron phosphate full battery at 0.5C and 1.0C, respectively. It can be seen that the Li|LLZTO|LFP battery can only cycle 60 and 12 times at 0.5C and 1.0C, respectively, with an initial capacity of 123.5 mAh g -1 and 18.5mAh g -1 The capacity of Li-Ag|LLZTO|LFP battery at 0.5C is 147.0mAh g -1 After 83 cycles, the capacity decayed rapidly and the battery failed. At a higher rate of 1.0C, the battery capacity continued to decrease, and after 90 cycles, it was only 7.1 mAh g -1 In contrast, the Li-Ag|PD-LLZTO|LFP full cell with a porous solid electrolyte structure has a discharge capacity of 150.3 mAh g at 0.5C.-1 After 400 stable cycles, the capacity retention rate is 98.7%. Even at 1.0C, the Li-Ag|PD-LLZTO|LFP full cell has a capacity of 130.2 mAh g -1 The porous electrolyte provides a stable ion permeation pathway, increases the anode ion migration depth, improves the electrode reaction kinetics, and relieves the anode stress / strain, thus achieving excellent cycling performance.
[0076] Example 2
[0077] Different from Example 1, in Example 2, Na3Zr2Si2PO 12 The solid electrolyte uses PVDF-HFP as the pore-forming agent with a mass ratio of 3:1. The molten salt material used to modify the porous layer is SnF2. The powder masses of the porous layer and the dense layer are 50 mg and 150 mg, respectively. This makes the critical current density of the sodium symmetric battery as high as 1.5 mA cm -2 The relevant experimental data are shown in Table 1.
[0078] Example 3
[0079] In Example 3, β″-alumina is used as the solid electrolyte, starch is used as the pore-forming agent, the mass ratio is 2:1, the molten salt material used to modify the porous layer is SnCl4, the powder masses of the porous layer and the dense layer are 70 mg and 150 mg respectively, so that the critical current density of the potassium symmetric battery is as high as 1.8 mA cm -2 The relevant experimental data are shown in Table 1. It should be noted that in other embodiments, other solid electrolyte powders and pore-forming agents may also be used. The mass of the porous layer powder may also be 80 mg, 100 mg, etc. The mass of the dense layer powder may also be 200 mg, 300 mg, 500 mg, etc.
[0080] The molten salt material may also be other commonly used molten salt materials as long as they meet the required melting point and decomposition temperature.
[0081] Comparative Example 1
[0082] Different from Example 1, only conventional Li 6.4 LqCy 1.4 Ta 0.6 O 12 As a solid electrolyte, the relevant experimental data are shown in Table 1 and Fig.11 shown.
[0083] Table 1 Experimental data of embodiments and comparative examples
[0084]
[0085] It can be seen that the solid-state alkali metal battery constructed in the embodiment of the present invention can significantly improve the diffusion rate and utilization rate of the alkali metal negative electrode, and achieve high current density (>1.0mA cm -2 ), large area capacity (>0.5mAh cm -2 ) under stable cycle (> 1600h), such as Fig.11 As shown in (b) in .
[0086] In summary, the present invention can solve the problems of discontinuous ion conductive network inside the alkali metal negative electrode and low bonding strength with the solid electrolyte, and provides a simple and easily expandable surface modification method based on molten salt, avoiding the use of expensive and complex surface coating technology, significantly improving the non-wetting problem between the ion conductive network and the alkali metal, achieving the purpose of improving the utilization rate of the negative electrode alkali metal, thereby realizing the stable circulation of solid-state alkali metal batteries at high current density and large area capacity.
[0087] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a modified porous-dense solid electrolyte, characterized in that: include: Spreading a molten salt material onto the surface of a porous layer of a porous-dense solid electrolyte, and performing a first heating until the molten salt material is melted; wherein the porous-dense solid electrolyte comprises a porous layer and a dense layer composed of solid electrolyte powder; After the molten salt material is melted, it is heated for a second time to decompose the molten salt material. The decomposed product of the molten salt material adheres to the surface of the porous layer to obtain a modified porous-dense solid electrolyte.
2. The method for preparing a modified porous-dense solid electrolyte according to claim 1, characterized in that: The melting point of the molten salt material is 50°C to 500°C, and the decomposition temperature is 100°C to 700°C.
3. The method for preparing a modified porous-dense solid electrolyte according to claim 1, characterized in that: The preparation process of the porous-dense solid electrolyte comprises: The solid electrolyte powder and the pore former are stirred and mixed in an organic inert solvent, and then the organic inert solvent is evaporated to obtain a mixed powder; Adding solid electrolyte powder to a tablet pressing mold and pressing it into a tablet as a dense layer precursor; evenly spreading the mixed powder on the surface of the dense layer precursor and pressing it into a green blank; wherein the mixed powder forms a porous layer precursor during the pressing process; The green body is sintered to form a porous-dense solid electrolyte consisting of a porous layer and a dense layer.
4. The method for preparing a modified porous-dense solid electrolyte according to claim 3, characterized in that: The proportion of the pore former in the mixed powder is 10 wt % to 33.3 wt %.
5. The method for preparing a modified porous-dense solid electrolyte according to claim 3, characterized in that: The amount of porous layer powder used is 50mg to 100mg, and the amount of dense layer powder used is 100mg to 500mg.
6. The method for preparing a modified porous-dense solid electrolyte according to claim 3, characterized in that: The solid electrolyte is a garnet-type oxide, β″-alumina, NASICON-type, argyrodite-type, alkali metal nitride or LiPON-type solid electrolyte; The pore-forming agent is polyethylene oxide, polymethyl methacrylate, polyacrylonitrile, polyvinyl chloride, polyvinyl alcohol, polyvinyl acetate, polyacrylic acid, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, chitosan, methyl cellulose, starch, FeCl3, AlCl3, BiCl3, SbF3, SbCl3, S or SeS2.
7. A modified porous-dense solid electrolyte, characterized in that: The modified porous-dense solid electrolyte is prepared by the modified porous-dense solid electrolyte preparation method according to any one of claims 1 to 6.
8. A method for preparing a composite alkali metal negative electrode, characterized in that: include: The alkali metal is heated to a molten state and poured onto the surface of the porous layer of the modified porous-dense solid electrolyte to obtain a composite alkali metal negative electrode; Wherein, the modified porous-dense solid electrolyte is prepared by the modified porous-dense solid electrolyte preparation method described in any one of claims 1 to 6, or is the modified porous-dense solid electrolyte described in claim 7.
9. The method for preparing a composite alkali metal negative electrode according to claim 8, characterized in that: The alkali metal is lithium, sodium or potassium.
10. A composite alkali metal negative electrode, characterized in that: The composite alkali metal negative electrode is prepared by the composite alkali metal negative electrode preparation method according to claim 8 or 9.
Citation Information
Patent Citations
Porous core-shell structure negative electrode material, preparation method and battery thereof
CN106558685A
Alkali metal solid-state battery interface modification method based on low-temperature molten salt and application
CN114300767A
Melting point regulation and control positive electrode layer and preparation method and application thereof
CN117438529A
Cycling stability of Li-ion battery with molten salt electrolyte
US20060147795A1
Solid electrolyte material, electrode, battery, battery pack, and vehicle
US20200295400A1
